Association between Left Ventricular Global Longitudinal Strain and Functional Capacity Measured with Six-Minutes Walk Test in Patients after Acute Myocardial Infarction. - Wasyanto, Trisulo; Wulandari, Pipiet; Purwaningtyas, Niniek; Murti, Bhisma (Indonesian Journal of Medicine, 2017)
Background: The ischemia resulting from critical coronary narrowing or total occlusion first affects the subendocardialmyofibers. Thus, abnormalities in longitudinal function can be detected before reductions in LVEF and reflects infarct size. The 6MWT provides information that may be a better index of the patients ability to perform daily activities. This study was to assess the relationship between left ventricular (LV) global longitudinal strain (GLS) and functional capacity measured with 6 minute walk test (6MWT) after AMI.Subjects and Method: This is a cross sectional study of patients with STEMI and NSTEMI, at Moewardi Hospital, Surakarta. Eligible patients underwent echocardiography global longitudinal 2D-STE that performed within 48 hour of admission and 6MWT pre- discharge or at the first follow-up visits (day 4-9). Patients were divided into 2 groups according to the LV GLS value, patients with substantial infarction (LV GLS > -13.8%) and non-substantial infarction (LV GLS < -13.8%).Results: There were 50 patients with 42 STEMI and 8 NSTEMI. Compared to patients in group LV GLS < -13.8% (n=18), patients in group LV GLS > -13.8% (n=32) were more likely to be older (57.6 y.ovs 55 y.o), less in functional capacity (10.17 1.3 ml/kg/min vs 11.04 0.98 ml/kg/min; p= 0.018) and less in 6 MWT distance (347.97 65.49 m vs392.39 49.44 m; p=0.016). Using ROC curves, the 6 MWT distance cutoff value of 375 m identified patients with LV GLS >-13.8%, sensitivity of 72.2% and specificity 65.6%, respectively with AUC= 0.70 (CI 95%; 0.559-0.852; p= 0.017). However, LV GLS >-13.8% and age >60 y.o remained the independent predictor in a multivariate logistic regression analysis to identify 6 MWT distance < 375 m in patients after AMI with GLS >-13.8%, (OR =7.967; CI 95%= 1.669-38.030; p=0.009) and age >60 y.o, (OR=10.898; CI95%= 2.201-53.971; p=0.003).Conclusions: In patients after AMI with substantial infarction (LV GLS >-13.8%) had less in functional capacity. The 6 MWT distance cutoff value of 375 m identified patients with LV GLS >-13.8% and could be used in rehabilitation program after AMI.Keywords: Acute Myocardial Infarction, LV Global longitudinal strain, functional capacity, 6 MWT.Correspondence:Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java.Indonesian Journal of Medicine (2017), 2(3): 192-206https://doi.org/10.26911/theijmed.2017.02.03.07